Antimicrobial properties of tannin extracts against the phytopathogenic oomycete Plasmopara viticola - Anthony Pébarthé-Courrouilh; Michael Jourdes; Mathilde Theil-Bazingette; Anne-Laure Gancel; Pierre-Louis Teissedre; Josep Valls-Fonayet; Stephanie Cluzet (OENO One)
Downy mildew (Plasmopara viticola) is one of the most devastating diseases for European grapevines (Vitis vinifera L.), requiring extensive use of copper-based or synthetic pesticides. Due to the negative effects of these products (e.g., impacts on environment and human health, acquisition of pathogen resistance), there is a crucial need to develop alternative strategies for controlling downy mildew in the vineyard. Tannins are compounds that are directly toxic to diverse microorganisms, but little is known about their antimicrobial activities against grapevine pathogens. The aim of our study was therefore to explore the anti-oomycete activities of tannins extracts originating from by-products of four different botanical sources (nut gall, chestnut wood and, grape skin and seeds) in order to help promote a circular economy. We first characterised these five extracts and found that the chemical composition of the tannin extract depended highly on its botanical source. We then tested their in vitro antimicrobial activities against P. viticola: two grape seed tannin extracts (a homemade and a commercial extract), showed promising inhibitory activity against downy mildew sporulation at 400 mg/L. The IC50 (concentration inhibiting 50 %) of each of these two extracts were thus determined for their inhibition of P. viticola sporulation, zoospore motility and zoospore release from sporangia. The results showed that the homemade grape seed extract was more active against P. viticola than the commercial one. Finally, the homemade grape seed extract was fractioned based on the polymerisation degree (mDP) of condensed tannins, and the three fractions generated were tested for their capacity to inhibit the sporulation of the oomycete. The fraction containing procyanidins with higher mDP values was noted as the most antimicrobial (96 % inhibition at 400 mg/L). Thus, grape seed extracts rich in procyanidins of high mDP could represent a promising solution for controlling downy mildew.